Pemodelan Matematika Terhadap Keuntungan Bulanan Pada Wartel Asrama Ma’hadul Qur’an Pondok Pesantren Salafiyah Syafi'iyah Sukorejo - Ahmad Ainul Yaqin; Mohammad Tohir (LP2M Universitas Ibrahimy, 2023)
This study aims to determine the mathematical modeling of monthly profits at the Ma'hadul Qur'an boarding school kiosk located at the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo. The research method used is a quantitative descriptive method using numbers, and the analysis uses statistical methods. The results of the research show that (1) the solution for students who are limited in communicating with other people by using the telephone is the holding of a pesantren kiosk; (2) The shop is an attempt by the pesantren to help its students who cannot bring their cell phones to the pesantren because of a ban; (3) Wartel standard tariff is Rp2000 per minute, the monthly fee per call is Rp62,000, and all 5 telephone units; (4) The total income from the first week to the last week is 2.207.500, the total expenses are Rp310.000. Thus if it is calculated, it will produce a net profit of 1,800,000. Meanwhile, the minimum profit is 1,590,000, and the maximum profit is 2.312.000; and the Mathematical Modeling is Y = (X_1 + X_2 + X_3 + X_4 ) - (5 × 62,000).